A comparative study of high school mathematics teachers’ audible teaching language: A student satisfaction perspective - Jiang, Peijie; Zhang, Xiangjun; Ruan, Xiaomeng; Feng, Zirong; Xiong, Bin; Jiang, Yanyun (Frontiers in Psychology, 2023)
Teachers’ audible teaching language is essential for organizing classroom instruction. An audible teaching language is a form of language that transmits knowledge through sound and emphasizes the impact of the teacher's vocal qualities on the effectiveness of the classroom. This study used a questionnaire to compare expert, skilled, and novice high school mathematics teachers’ audible teaching language from the perspective of student satisfaction. The sample was selected using a purposive sampling technique, and the participants were students from a key high school in Changsha, China. A research framework and research instrument with good reliability and validity were constructed for this study. The data were analyzed using SPSS 22.0 and AMOS 22.0. The results showed 263 valid questionnaires, good measurement model fit, and high reliability and validity of the questionnaire. It was found that: 1) students were highly satisfied with the audible teaching language of high school mathematics teachers; 2) student satisfaction with the audible teaching language of skilled, expert, and novice mathematics teachers declined in order, but there was no significant difference overall; 3) students were more satisfied with expert mathematics teachers than with novice teachers in terms of the tone and adaptability of the audible teaching language. The researcher discussed the study’s results, suggested how pre-service and post-service mathematics teachers can improve the quality of their audible teaching language, and pointed out the value and limitations of the study.